2015
DOI: 10.1007/s11239-015-1305-4
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications in venous thrombosis patients on well-managed warfarin

Abstract: Anticoagulation treatment is effective in preventing both death and recurrence in patients with venous thromboembolism (VTE), but at the same time confers a substantial risk of bleeding complications. The aim of this study was to examine the rate of and predictors for bleeding complications in VTE patients on warfarin with high treatment quality. In total 13,859 patients on warfarin for VTE between January 1st 2006 and December 31th 2011 were retrieved from the national quality register Auricula. The cohort wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
10
2
Order By: Relevance
“…Despite the relatively high mean age of 65.3 years in our study, the rate of clinically relevant bleeding was comparable to that found in the dabigatran arm in RE-COVER and RE-COVER II studies at 4.3 major bleedings per 100 treatment years (15). In these studies the mean age was lower at 54.8 years with age being a known risk factor for bleeding complications (8,16), TTR were also lower at 57 % compared to 68.9 % found here which may be an explanation to the low rate of bleeding complications. However, with a difference in endpoint definitions where we lack information about fall in haemoglobin and transfusion a direct comparison to these studies is difficult.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…Despite the relatively high mean age of 65.3 years in our study, the rate of clinically relevant bleeding was comparable to that found in the dabigatran arm in RE-COVER and RE-COVER II studies at 4.3 major bleedings per 100 treatment years (15). In these studies the mean age was lower at 54.8 years with age being a known risk factor for bleeding complications (8,16), TTR were also lower at 57 % compared to 68.9 % found here which may be an explanation to the low rate of bleeding complications. However, with a difference in endpoint definitions where we lack information about fall in haemoglobin and transfusion a direct comparison to these studies is difficult.…”
Section: Discussioncontrasting
confidence: 39%
“…Both in the group with high iTTR and the group with low INR variability the patients were older (▶ Table 1), but they also had less concomitant diseases. Some of the previous conditions known to increase the risk of bleeding complications among warfarin treated patients as anaemia, cardiac failure, previous major bleeding and chronic pulmonary disease were more prevalent among those with poorer INR control (8).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…False positive bleeding rates is also likely when based on administrative ICDcodes without a complementary chart review [18,19]. A similar study to this using administrative ICD-10 codes for estimating bleeding rates, but with real life data on warfarin with well-regulated TTR instead of NOACs in treatment for venous thromboembolism found a lower risk of major bleeding and reported a major bleeding rate of 2.36 per 100 treatment years [8]. This might be due to a slightly older Events per 100 patients years Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Given the above discussed risks, patients with unprovoked VTE should receive ‘lifelong’ anticoagulation. Nevertheless, the guidelines recommend that extending the therapy must incorporate a balance of the VTE recurrence risk with the risk of bleeding associated with anticoagulant therapy and continue therapy until bleeding risks outweigh the benefits of reducing recurrence …”
Section: Discussionmentioning
confidence: 99%